Late Adolescent Emotional Intelligence Analysis Based on Gender - Endang Mei Yunalia; Arif Nurma Etika (Universitas Muhammadiyah Semarang, 2020)
Changes in psychological aspects that on adolescents can affect the formation of positive or negative behavior. The ability of adolescents to express feelings and manage emotions appropriately is the role of emotional intelligence.emotional intelligence inmale and female adolescents has different characteristics. This research was conducted to knowingthe relationship between emotional intelligence and gender in late adolescents.this research is a correlational analytic study conducted on 191 respondents who were selected using simple random saling method on Faculty of Health Sciences, Kadiri University students. Emotional intelligence data obtained from respondents using Emotional intelligence questionnaire adapted from Goleman theory. Data processed using correlation coefficient contingency test. The result was Sig value = 0,231 < 0,05 its mean any correlation about emotional intelligence and gender in late adolescents. The results of this study are used as information for nurses, adolescents and parents.